Pendekatan Desain Arsitektur Tepi Air Kawasan Danau Sipin - Algusrinof Algusrinof; Zulherman Zulherman; Jonny Wongso (Jurnal Talenta Sipil, 2023)
The research location is the Sipin Lake Area in Jambi City Center. Precisely located in Legok Village, Lake Sipin District, Jambi Province. According to current observations, Lake Sipin's friends are experiencing a degradation in the quality of the spatial direction of the slum area where activities are only functional, namely residential areas. This paper basically aims to support the government's program in developing the Lake Sipin area into an ecotourism area by structuring the waterfront area around the Lake Sipin area with an approach from an architectural design perspective which is carried out by structuring the area by adding new functions through analysis that will conceptualized through regional characteristics, potentials and problems of the Sipin Lake area. This research is expected to contribute to providing solutions in the development of the Lake Sipin Waterfront Area.